2018
DOI: 10.48550/arxiv.1805.03924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased and Consistent Nested Sampling via Sequential Monte Carlo

Abstract: We introduce a new class of sequential Monte Carlo methods called Nested Sampling via Sequential Monte Carlo (NS-SMC), which reframes the Nested Sampling method of Skilling (2006) in terms of sequential Monte Carlo techniques. This new framework allows convergence results to be obtained in the setting when Markov chain Monte Carlo (MCMC) is used to produce new samples. An additional benefit is that marginal likelihood estimates are unbiased. In contrast to NS, the analysis of NS-SMC does not require the (unrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…Recent work has proposed adapting the MCMC kernel parameters online using the population of particles. For example, Fearnhead and Taylor (2013) and Salomone et al (2018) propose adaptation methods for generic MCMC kernels. Buchholz et al (2018) propose methods for performing the notoriously challenging tuning of HMC kernel parameters in SMC.…”
Section: Sequential Monte Carlo and Control Variatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has proposed adapting the MCMC kernel parameters online using the population of particles. For example, Fearnhead and Taylor (2013) and Salomone et al (2018) propose adaptation methods for generic MCMC kernels. Buchholz et al (2018) propose methods for performing the notoriously challenging tuning of HMC kernel parameters in SMC.…”
Section: Sequential Monte Carlo and Control Variatesmentioning
confidence: 99%
“…This example has been considered from a Bayesian context in Girolami (2008), South et al (2018) and Salomone et al (2018). Following South et al (2018), observations y(t) of R pp (t) are observed with noise such that y(t) ∼ N (R pp (t), 0.02 2 ) for t = 0, 3, .…”
Section: Odementioning
confidence: 99%
See 2 more Smart Citations
“…,Salomone et al (2018) andBon et al (2021) for examples of this idea outside of the exact-approximate context. The conditional ESJD is defined as…”
mentioning
confidence: 99%